POTENSI PENGEMBANGAN PISANG ABAKA (Musa textilis Nee) DI PULAU KARAKELANG - Marselina Nebangka; Berce.R.A Sumayku; Jantje Pongoh (Universitas Sam Ratulangi, 2019)
ABSTRAC This study aims to determine the development of Abaka bananas (Musa textilis Nee) on Karakelang Island. The results of this study are expected to provide information, for Farmers in the Development of Abaca banana cultivation, on Karakelang Island. in addition, it can support the overall development of Abaca banana cultivation in Talaud Islands Regency. This research was conducted for three months, from December 2018 to March 2019, the location of sampling in Karekelang Island in three districts, namely: Essang District, Essang Selatan District, and Beo Utara District and in each subdistrict each was selected four Village. In each village there are ten Abaka respondents / farmers. This research was conducted by survey using a questionnaire with direct interviews to farmers. The results of the study show that Abaca (rotte) is an endemic Talaud plant which is very suitable for the climate and soil on the karakelang island, with the cultivation system of farmers still traditionally, There is no excessive treatment for Abaca bananas. Farmers intercropping with coconut and durian plants. Excellence Karakelang Island has five regional superior varieties. Planting distance applied by farmers varies greatly, namely 4m x 4m, 4.5m x 4.5m, 5m x 5m while others are still dependent on coconut and Durian as the main crop. Abaca on Karakelang Island can be cultivated at altitudes below 300 m asl which are found in the three research location Districts. Keyword: Potential, Abaka Banana, Development, Karakelang